1997
DOI: 10.1111/j.1751-1097.1997.tb07962.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐dependent Oxygen Consumption in Bacteriochlorophyll‐Serine‐treated Melanoma Tumors: On‐line Determination Using a Tissue‐inserted Oxygen Microsensor

Abstract: Successful application of anticancer therapy, and especially photodynamic therapy (PDT) mediated by type I1 (PDTII) processes, depends on the oxygen content within the tumor before, during and after treatment. The high consumption of oxygen during type I1 PDT imposes constraints on therapy strategies. Although rates of oxygen consumption and repletion during PDTII were suggested by theoretical studies, direct measurements have not been reported. Application of a novel oxygen sensor allowed continuous and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 27 publications
5
43
0
1
Order By: Relevance
“…It was confirmed results of morphological study (Fig.12) of tumor after PDT, which have shown a strong vascular damages (hemorrhages (A) and thrombosis (B)) as well as expressed necrosis (A,B) and apoptosis (C) of malignant tissue. These results are in a good agreement with the data of J. Zilberstein et al 5,6 .…”
Section: Investigation Of a Photodynamic Efficiency And Photobleachinsupporting
confidence: 83%
See 2 more Smart Citations
“…It was confirmed results of morphological study (Fig.12) of tumor after PDT, which have shown a strong vascular damages (hemorrhages (A) and thrombosis (B)) as well as expressed necrosis (A,B) and apoptosis (C) of malignant tissue. These results are in a good agreement with the data of J. Zilberstein et al 5,6 .…”
Section: Investigation Of a Photodynamic Efficiency And Photobleachinsupporting
confidence: 83%
“…The spectra of tumor fluorescence were investigated before and after irradiation in order to estimate the photo-bleaching of Bchl-Ser in vivo. The level of blood oxygenation in tumor vessels was measured during all time of irradiation and continuing for approximately 10 minutes after it was finished using method described by J. Zilberstein et al 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism has been proven in preclinical and clinical settings (11,17,19,36,37). Of particular relevance to our study is a report by Foster et al (38), which investigated tumor response to various irradiation regimens composed of constant 2-h duration.…”
Section: Discussionmentioning
confidence: 79%
“…Based on the findings presented in this study, the therapeutic effectiveness of the Bchl-ser-PDT þ HT treatment is mediated by a rapidly induced vascular stasis, which in turn can lead to the tumour cells being deprived of O 2 and nutrients. In earlier studies in which the effects of Bchl-ser-PDT alone were monitored in tumour tissue, PDT-induced O 2 consumption (Zilberstein et al, 1997) and changes indicative of vascular stasis (Zilberstein et al, 2001) were also found. While vascular damage has frequently been described as a consequence of PDT, it is not a primary target when PDT is applied in the clinical oncology setting, since, as with ionising radiation and some chemotherapy agents, the PDT effect is O 2 -dependent (Höckel and Vaupel, 2001) and thus, O 2 deprivation due to vascular damage may reduce the treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%